The Geometroidea (Lepidoptera) from Cuba described by Herrich-Schäffer in the Gundlach collection, Havana - Becker, Vitor Osmar (2002)
The taxonomic status of 35 nominal species of Geometroidea from Cuba described by Herrich-Schäffer is discussed. Type material of 33 nominal species preserved in Coll. Gundlach, Instituto de Ecología y Sistemática, Havana, is evaluated. Thirty four species names are recognized, 11 species names are synonymized, six new combinations, six reinstated synonymies and four species recalled from synonymy are established, and one new species is proposed.